2006
DOI: 10.1073/pnas.0604056103
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants reduce cone cell death in a model of retinitis pigmentosa

Abstract: Retinitis pigmentosa (RP) is a label for a group of diseases caused by a large number of mutations that result in rod photoreceptor cell death followed by gradual death of cones. The mechanism of cone cell death is uncertain. Rods are a major source of oxygen utilization in the retina and, after rods die, the level of oxygen in the outer retina is increased. In this study, we used the rd1 mouse model of RP to test the hypothesis that cones die from oxidative damage. A mixture of antioxidants was selected to tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
373
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 372 publications
(394 citation statements)
references
References 31 publications
21
373
0
Order By: Relevance
“…Using a transgenic pig model of RP and immunohistochemical markers for oxidative damage, the hypothesis that cones undergo progressive oxidative damage after the death of rods was tested and found to be correct . In rd1 mice, it was found that daily administration of a mixture of antioxidants was able to substantially ameliorate oxidative damage after death of rods and significantly reduced cone cell death (Komeima et al, 2006). Similar findings were obtained in the Q344ter mouse model of ADRP and rd10 mice, a model of more slowly progressive autosomal recessive RP.…”
Section: Photoreceptor Cell Death In Rpsupporting
confidence: 70%
“…Using a transgenic pig model of RP and immunohistochemical markers for oxidative damage, the hypothesis that cones undergo progressive oxidative damage after the death of rods was tested and found to be correct . In rd1 mice, it was found that daily administration of a mixture of antioxidants was able to substantially ameliorate oxidative damage after death of rods and significantly reduced cone cell death (Komeima et al, 2006). Similar findings were obtained in the Q344ter mouse model of ADRP and rd10 mice, a model of more slowly progressive autosomal recessive RP.…”
Section: Photoreceptor Cell Death In Rpsupporting
confidence: 70%
“…On the other hand, RIP1 forms a complex with NADPH oxidase 1 and TNF-R1-associated death domain and produces superoxide, which in turn leads to induction of necrosis (41). In animal models of RP, Campochiaro and colleagues have demonstrated that retinal oxidative stress increases especially in the period of cone degeneration and that antioxidant treatments delay cone cell death (28,40).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of cone cell death in RP are less well characterized. Although loss of rodderived trophic factors (27), oxidative stress (28), and nutrient starvation (29) are shown to contribute to the cone degeneration, little is known about the cell death types and molecules that mediate cone cell death.…”
mentioning
confidence: 99%
“…After rods die, oxygen consumption in the outer retina is markedly reduced, and tissue oxygen levels become substantially elevated (6). This results in progressive oxidative damage to cones and gradual cone cell death, which can be slowed by antioxidants (7). The antioxidant defenses include vitamins, minerals, and the antioxidant enzymes glutathione, superoxide dismutase, hydrogen peroxidase, catalase, and thioredoxins (8).…”
mentioning
confidence: 99%